Counterinsurgency in a Test Tube Analyzing the Success of the Regional Assistance Mission to Solomon Islands (RAMSI) - Glenn, Russell W. (RAND Corporation, 2007)
The Regional Assistance Mission to Solomon Islands (RAMSI), which began on July 24, 2003, has been a remarkable success, in part because of the consistency of its message, the strength of its leadership, and its uncommon support for, rather than overt control of, the Solomon Islands government and policing capability. This study reviews RAMSI operations through the lens of a broader application to current and future counterinsurgency efforts.